THE INFLUENCE OF COMPENSATION, MOTIVATION, AND WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Saputra, Hellen Monica Ghaby Ayu; Jaya, Tiara Juliana (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Competition between companies encourages increased awareness of the importance of high-quality and committed human resources as the main factor in achieving the company's vision, mission, and goals. Good employee performance is driven by adequate compensation and motivation and balancing work and personal life (work-life balance), increasing job satisfaction. This research investigates the influence of compensation, motivation, and work-life balance on employee performance with job satisfaction as an intervening variable, especially in the context of Bank Tabungan Negara (BTN) Syariah employees in Malang City. This research uses quantitative methods with data collection techniques through interviews, questionnaires, literature, and data analysis using Structural Equation Modeling (SEM). The subjects in this research were 43 employees of Bank BTN Syariah Malang City. The research results show that job satisfaction has no significant effect on employee performance due to limited promotions, while compensation has a significant positive effect on job satisfaction through motivation. Motivation and Work-Life Balance each have a significant influence on employee performance, with motivation encouraging optimal performance and work-life balance increasing job satisfaction and motivation. However, job satisfaction does not act as a significant intervening variable between compensation, motivation, Work-Life Balance, and employee performance.